الهوية البشرية المركبة والتعدد الثقافي عند إدغار موران - بلخضر، وحيد; دراس، شهرزاد (جامعة وهران2 محمد بن أحمد, 2020)
Culture identity, considers like an important subject by sophists in civilization of nowadays, specifically it's suffered by many dilemmas caused by mistakes of Isolation, simplification and reduction, all of this it's named (blind intelligence). In language of French philosopher Edger Morin. This philosopher was against human brutality and barbarity which producted by modern rationality, in same time he has put other theory of rationality, its purpose constitute in the knowledge of humanism true which based on Composite Ground Identity, where it spoke about the variety and diversity, in order to complete a good environment of culture in this planet.
يعد موضوع الهوية الثقافية من الموضوعات التي نالت حظا وافرا من اهتمام المفكرين في حضارة اليوم خصوصاً وأنها تشهد على أمراض متعددة، ناتجة عن أخطاء العزل والتبسيط والاختزال، هذه الأمراض كلها ترد إلى ما يسمى بالذكاء الأعمى بلغة الفيلسوف الفرنسي إدغار موران الذي يجد نفسه أمام رهان الاعتراض على وحشية الإنسان المعاصر وبربريته التي أنتجتها العقلانية الحداثية، وأمام التنظير إلى عقلانية مغايرة منفتحة يستهدف من خلالها بلوغ الطبيعة البشرية الحقيقية القائمة على الهوية الأرضية المركبة، التي تراعي مبدأ التعدد والاختلاف من أجل إغناء الخليط الثقافي الكوكبي.
Keywords: الهوية الثقافية -- موران، إدغار -- الفكر الفلسفي -- الحداثة -- العولمة الثقافية